Penerapan Jurnalisme Lingkungan dalam Pemberitaan Sampah di Media Daring Selama Bulan Ramadhan (Analisis Isi Kuantitatif terhadap Pemberitaan Sampah di Media Daring Detik.com dan Republika Tahun 2021-2023) - Akbar, Wilon Tri (LPPM Institut Pendidikan Nusantara Global, 2024)
Increased waste volumes during the month of Ramadan can cause significant environmental impacts, especially pollution and contamination. This needs to be reported by the media, especially online media, so that the public knows the negative impacts of increasing waste volumes using the principles of environmental journalism. This research aims to find out how the principles of environmental journalism are applied regarding reporting on waste in the month of Ramadan in Detik and Republika media using the four principles of environmental journalism. The four principles are the principles of sustainability, biocentrism, environmental justice and professionalism. The news selected to be researched using this analysis method is all news on the online media Detik.com and Republika for the period 2021-2023. The analytical method used is quantitative content analysis. The research results show that the application of environmental journalism to the sustainability principles of Detik.com media is 39.6% which is in the low category and Republika media is 39.6% which is in the medium category. The application of the biocentric principle of Detik.com media was 15.6% which was in the very low category and Republika media was 12.5% ​​which was in the medium category. Detik.com media's application of environmental justice principles was 16.6%, which was in the very low category, Republika media was 20.8%, which was in the low category. Then the application of the principle of professionalism of Detik.com media was 58.3% which was in the medium category and Detik.com media was 43.7% which was in the medium category.